General practitioners' awareness of the recommendations for faecal immunochemical tests (FITs) for suspected lower gastrointestinal cancers: a national survey. - Von Wagner, C; Stoffel, S; Freeman, M; Laszlo, H; Nicholson, B; Sheringham, J; Szinay, D; Hirst, Y (BMJ Publishing Group, 2019)
OBJECTIVES:In July 2017, UK National Institute for Health and Care Excellence (NICE) published a diagnostic guidance (DG30) recommending the use of faecal immunochemical tests (FITs) for symptomatic patients who do not meet the urgent referral pathway for suspected colorectal cancer (CRC). We assessed general practitioners' (GP) awareness of DG30 in primary care 6 months after its publication. DESIGN AND SETTING:Cross-sectional online survey of GPs hosted by an English panel of Primary health care professionals. PARTICIPANTS:In December 2017, 1024 GPs registered on an online panel (M3) based in England took part in an online survey. OUTCOMES AND VARIABLES:We investigated a number of factors including previous experience of using FIT and guaiac faecal occult blood tests (FOBTs), the number of urgent referrals for CRC that GPs have made in the last year and their sociodemographic and professional characteristics that could be associated with their self-reported awareness of the FIT diagnostic guidance. RESULTS:Of the 1024 GPs who completed the survey, 432 (42.2%) were aware of the current recommendation but only 102 (10%) had used it to guide their referrals. Awareness was lowest in North West England compared with London (30.5% vs 44.9%; adjusted OR: 0.55, 95% CI 0.33 to 0.92). Awareness of the FIT guidance was positively associated with test usage after the NICE update (adjusted OR: 13.00, 95% CI 6.87 to 24.61) and having specialist training (adjusted OR: 1.48, 95% CI 1.05 to 2.08). The number of urgent referrals, the previous use of FOBt, GPs' age and gender, work experience and practice size (both in terms of the number of GPs or patients at the practice) were not associated with awareness. CONCLUSIONS:Less than half of GPs in this survey recognised the current guidance on the use of FIT. Self-reported awareness was not systematically related to demographic of professional characteristics.